2017
DOI: 10.1016/j.jdiacomp.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Silent coronary heart disease in patients with type 2 diabetes: application of a screening approach in a follow-up study

Abstract: An abnormal ECG was a strong, independent predictor of silent CHD (OR 8.9; CI 1.27-62.5; p=0.028) in DM2. Therefore, a functional stress testing should be considered in DM2 patients with ECG abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…DM is an independent risk factor for patients with coronary heart disease. In patients with coronary heart disease combined with T2DM, the persistent chronic hyperglycemia in the body damages the blood vessel wall and endothelial cells, and the action of a variety of inflammatory cytokines leads to the formation of atherosclerotic plaques, thus resulting in or accelerating the occurrence and development of coronary heart disease and other atherosclerotic lesions ( 13 , 14 ). A number of studies in China and elsewhere indicated that there are correlations of serum PTX3, HbAlc and ApoA1/ApoB with the change in the condition of coronary heart disease or DM in patients and their prognoses ( 10 – 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…DM is an independent risk factor for patients with coronary heart disease. In patients with coronary heart disease combined with T2DM, the persistent chronic hyperglycemia in the body damages the blood vessel wall and endothelial cells, and the action of a variety of inflammatory cytokines leads to the formation of atherosclerotic plaques, thus resulting in or accelerating the occurrence and development of coronary heart disease and other atherosclerotic lesions ( 13 , 14 ). A number of studies in China and elsewhere indicated that there are correlations of serum PTX3, HbAlc and ApoA1/ApoB with the change in the condition of coronary heart disease or DM in patients and their prognoses ( 10 – 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal ECG was defined to be a strong, independent predictor of silent CAD (OR 8.9; CI 1.27-62.5; p=0.028) in T2DM (Vigili de Kreutzenberg et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pathological Q waves were independently associated with a high-risk scan in the American study by Rajagopalan et al [39]. In a more recent, small, Italian study, an abnormal ECG was the strongest, independent predictor of silent CAD in 102 asymptomatic T2DM individuals (OR 8.9, CI 1.27-62.5; P = 0.028) [92].…”
Section: Factors Associated With Silent Coronary Artery Disease In Tymentioning
confidence: 93%